What affects international migration of European science and engineering graduates? - Andries de Grip; Didier Fouarge; Jan Sauermann (Institute for the Study of Labor (IZA), 2009)
Using a dataset of science and engineering graduates from 12 European countries, we analyse the determinants of labour migration after graduation. We find that not only wage gains are driving the migration decision, but also differences in labour market opportunities, past migration experience, and international student exchange are strong predictors of future migration. Contrary to our expectations, job characteristics such as the utilisation of skills in the job and involvement in innovation hardly affect the migration decision. When analysing country choice, countries such as the USA, Canada and Australia appear to attract migrants due their larger R&D intensity. Moreover, graduates with higher grades are more likely to migrate to these countries.
urn:nbn:de:101:1-2009081030
Keywords: F22; J61; 330; Migration; university graduates; scientists & engineers; Akademische Berufe; Brain Drain; Wissenschaftler; Ingenieure; Internationale Arbeitsmobilität; Europa; Einwanderung; USA; Kanada; Australien